Demographic dividend-favorable policy environment in two pre-dividend African nations: review of national policies and prospects for policy amendments in Nigeria and Tanzania - Xiaomeng Chen; Neia Prata Menezes; Jean Christophe Rusatira; Carolina Cardona; Mojisola Odeku; Deanna Kioko; Jessica Castro; Charity Ibeawuchi; Joel Silas Lincoln; Deo Ng'wanansabi; Jacob Macha; Abubakar Msemo; et al. (BMC, 2023)
Abstract Background In collaboration with local partners, we reviewed 18 national policy documents across two sub-Saharan African countries identified as pre-dividend nations by the World Bank in 2017: Nigeria and Tanzania. Our aim was to assess national policies in pre-dividend countries and to determine whether national strategies were primed to capitalize on changing demographic structures, maximally attain the demographic dividend, and augment socio-economic growth. Methods We conducted policy reviews by focusing on five key sectors of the Gates Institute Demographic Dividend Framework: Family Planning, Maternal and Child Health, Education, Women's Empowerment, and Labor Market. This framework was developed as a tool for countries to apply targeted policies for accelerating the demographic dividend based on their demographic structure. For each component we used a comprehensive list of indicators, defined via a systematic literature review, through which we assessed national policies aimed at maximizing the demographic dividend. Results Between the two countries, we observed persistent gaps in policies targeting family planning. Although more comprehensive, policies addressing maternal and child health, education, women's empowerment, and labor market still lagged in their specificity and measurability. We identified specific policy amendments and alternatives that Nigeria and Tanzania could consider to mitigate these gaps. We also stress the importance of designing measurable policy initiatives across sectors. Conclusions Based on these recommendations, as Nigeria, Tanzania, and other pre-dividend nations start experiencing rapid demographic changes, they may consider implementing routine policy reviews to strengthen policies across the five key sectors and harness the benefits of a demographic dividend.